Auntie Tiger - Yep, Laurence, 1948-; Lee, Insu (New York : HarperCollinsPublishers, 2009)
A retelling of the classic fairy tale, "Little Red Riding Hood," in which Big Sister sets aside her differences with Little Sister to rescue her from a tiger in disguise.
Kirkus Review.
2.7
K-3
Keywords: Fairy tales; Fairy tales; Fairy tales; Fairy tales -- Adaptations; Tigers -- Fiction; China -- Fiction; Family life -- China -- Fiction